Nutritional Study of Picky Eaters: A Case Control Study - Biswas, Rana Kumar; Ghosh, Srabonti; Kabir, ARM Luthful (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Picky eating is a relatively common problem during childhood. Picky eating may cause parents considerable concern leading to physician visits and may cause conflict between parents regarding handling of their child’s eating behavior. Objectives: The present study was conducted to compare the nutritional status and daily calorie consumption among children with and without picky-eating-behavior. Methods: The present study was conducted out in the Department of Paediatrics, Sir Salimullah Medical College and Mitford Hospital, Dhaka and private chambers of paediatrician, general physician from July 2013 to December 2013. The case was defined as a child who had anorexia or took one or two favorite foods as explained by the parents in an otherwise healthy child with picky eating disorder, while a control was defined as a child without having picky eating disorder. Results: Thirty percent of the parents of cases complained that their children were not growing well as opposed to only 4% of the control group (p<0.05). Complaint of abdominal pain was considerably higher in the former group than that in the latter group (p<0.05). The history of forceful feeding was present in 20% of the cases compared to none in the control (p>0.05). The mean 24 hours intake of calorie was lower in the cases than that in the control, but the difference did not reach the level of significance (p>0.05). In terms of nutritional status very few children (8%) with picky eating behavior were wasted (low weight-for-height) (p>0.05). However, 26% of the picky-eaters were underweight in terms of BMI compared to 7% of the controls, but the difference was not statistically significant (p>0.05). Conclusion: The study concluded that the children with picky-eating-behavior are almost similar to their control counterparts in terms of nutritional status (wasting, stunting and BMI) and calorie consumption. DS (Child) H J 2021; 37(1): 59-63